Like it or not? The impact of online platforms on the productivity of incumbent service providers - Bailin Rivares, Albert; Gal, Peter N.; Millot, Valentine; Sorbe, Stéphane (Paris, 2019)
"This paper uses a novel empirical approach to assess if the development of online platforms affects the productivity of service firms. We build a proxy measure of platform use across four industries (hotels, restaurants, taxis and retail trade) and ten OECD countries using internet search data from Google Trends, which we link to firm-level data on productivity in these industries. We find that platform development supports the productivity of the average incumbent service firm and also stimulates labour reallocation towards more productive firms in these industries. This may notably reflect that platforms’ user review and rating systems reduce information asymmetries between consumers and service providers, enhancing competition between providers. The effects depend on platform type. “Aggregator” platforms that connect incumbent service providers to consumers tend to push up the productivity of incumbents, while more disruptive platforms that enable new types of providers to compete with them (e.g. home sharing, ride hailing) have on average no significant effect on it. Consistent with this, we find that different platform types affect differently the profits, mark-ups, employment and wages of incumbent service firms. Finally, the productivity gains from platforms are lower when a platform is persistently dominant on its market, suggesting that the contestability of platform markets should be promoted."